Análise de transcriptoma combinada com estudo de conjuntos de dados multiômicos na identificação de transcritos regulados pelo hormônio tiroidiano - Almeida, Robson José de (2020)
The thyroid is an endocrine gland that synthesizes two hormones called thyroid hormones (HT), T3 and T4, their systemic functions, are essential for the development and maintenance of the organism, acting effectively in cell metabolism. Clinical research by NGS provides high sensitivity on a high-throughput platform, producing torrential data for extensive genomic analysis. Metabolomics is a technique that assesses the concentration of molecules and substrates in a given situation of interest. Mitochondria regulate their quality control mechanisms in order to maintain tissue energy homeostasis in any condition. In our work, peripheral blood was the material of choice given the capacity of breadth of information that the new generation transcriptome can offer. This work was divided into two objectives: Primary objective: Characterization of mitochondrial genes differentially expressed in hypothyroidism and their correlation with the laboratory condition by analysis of transcriptomes, metabolomes, methylomomes and identification of TREs and secondary objective: Identification of differentially expressed genes seeking qualitatively and quantitatively identify the best analytical method in different tools and libraries. Each sequencing is a particular universe, a factor that defines strategies in bioinformatics that are most suitable for different studies, and for our library the best strategy was the common dispersion, trend dispersion and likelihood ratio test. We observed that miRNAs and snoRNAs exert an influence on differentially expressed mRNAs. In addition, the published metabolomics and methylome data suggest an extra genomic regulation that points to a biological tendency of the organism to seek equilibrium with a possible inefficiency of the exogenous hormone. The quantification of TREs can be important to legitimize gene expression in T3 efficiency or deficiency. Mitochondrial genes undergo changes in expression in hypothyroidism unlike the concept of stable genes.